Surgical treatment of cardiac echinococcosis: a case report - I. I. Chernov; D. Yu. Kozmin; V. V. Demetskaya; G. M. Magomedov; S. T. Enginoev (Российский кардиологический журнал)
Echinococcosis refers is a chronic disease caused by tapeworms of the order Cyclophyllidea. Echinococcal cysts increase in size slowly and are often asymptomatic, and the symptoms of cardiac echinococcosis are nonspecific, which in turn can make diagnosis difficult. Early diagnosis and surgical treatment of this disease is crucial to prevent severe complications. Considering that the heart is affected extremely rarely, we want to demonstrate the successful surgical treatment.